Efficacy of elbasvir and grazoprevir in participants with hepatitis C virus genotype 4 infection: A pooled analysis. (31st March 2018) - Asselah, Tarik; Reesink, Hendrik; Gerstoft, Jan; de Ledinghen, Victor; Pockros, Paul J.; Robertson, Michael; Hwang, Peggy; Asante‐Appiah, Ernest; Wahl, Janice; Nguyen, Bach‐Yen; Barr, Eliav; Talwani, Rohit; et al.
Abstract: Background & Aims: The aim of this integrated analysis was to assess the efficacy of the once‐daily combination of elbasvir 50 mg and grazoprevir 100 mg, with and without ribavirin in HCV genotype 4 (GT4)‐infected participants enrolled in the Phase 2/3 clinical programme with elbasvir/grazoprevir. Methods: Treatment‐naïve and treatment‐experienced participants 18 years of age or older with chronic HCV GT4 infection and baseline HCV RNA ≥10 000 IU/mL were included in the analysis. The analysis population was the full analysis set (FAS; all participants who received at least 1 dose of study medication) and a total of 155 HCV GT4 participants were evaluated. The primary endpoint was sustained virologic response at week 12 (SVR12; HCV RNA less than the lower limit of quantitation at 12 weeks after the completion of study therapy). Results: Overall, among GT4‐infected participants treated with 12 or 16 weeks of elbasvir/grazoprevir ± ribavirin, the SVR12 efficacy rates were 96.4% (107/111) in treatment‐naïve participants and 88.6% (39/44) in treatment‐experienced participants. The SVR12 rates were 96.0% (97/101) in treatment‐naïve participants treated with 12 weeks of elbasvir/grazoprevir and 100% (8/8) in treatment‐experienced participants treated with 16 weeks of elbasvir/grazoprevir plus ribavirin. Efficacy was not impacted by GT4 subtype. Conclusions: The regimens of 12 weeks of elbasvir/grazoprevir without ribavirin, and 16 weeks of elbasvir/grazoprevir plus ribavirin, were efficacious in HCV GT4‐infected treatment‐naïve and treatment‐experienced participants respectively. Baseline NS5A resistance‐associated substitutions did not impact the efficacy of elbasvir/grazoprevir in GT4‐infected participants.